Metal forming technology dissemination for economic empowerment of small and medium enterprises - Abdulah, Amri; Sukarman, Sukarman; Jatira, Jatira; Rajab, Dede Ardi; Anwar, Choirul; Heryana, Ghany; Shieddique, Apang Djafar; Irawan, Adhi Chandra; Setiawan, Yuda; Bachtiar, Mochamad Faisal; Riswandi, Muhammad Andi (Universitas Muhammadiyah Magelang, 2021)
This metal forming technology dissemination activity involved three partners from micro, small and medium enterprises (MSMEs) engaged in the metal forming industry in the village of Karangsentosa, Karangbahagia District, Bekasi Regency. The main problem faced by partners is the difficulty in designing dies for the combination of piercing and blanking processes. This difficulty resulted in the piercing and blanking processes being carried out separately, resulting in less efficient production performance and higher production costs, thus requiring a reverse engineering process for some of its products. The method used in this dissemination process was an experimental method by doing reverse engineering on one of the products produced, namely the ducting corner. The purpose of this metal forming technology dissemination is to assist partners in increasing the efficiency of the production process by combining piercing and blanking processes into one process. In this metal forming technology dissemination activity, efficiency has been carried out from nine stages of the production process to five production processes. The combination of blanking and piercing processes using 1.2 mm SPCC-SD material for the production of ducting corners requires a minimum power press machine capacity of 18.3 tons. Further dissemination will be carried out by combining the piercing, blanking and bending processes by applying the progressives dies design.